바이오매스 유래 함산소 화합물의 수첨탈산소 촉매 반응: 총설 - 하정명(Jeong-Myeong Ha) (Clean Technology, 28(2), 2022)
Biomass is a sustainable alternative resource for production of liquid fuels and organic compounds that are currently produced from fossil fuels including petroleum, natural gas, and coal. Because the use of fossil fuels can increase the production of greenhouse gases, the use of carbon-neutral biomass can contribute to the reduction of global warming. Although biological and chemical processes have been proposed to produce petroleum-replacing chemicals and fuels from biomass feedstocks, it is difficult to replace completely fossil fuels because of the high oxygen content of biomass. Production of petroleum-like fuels and chemicals from biomass requires the removal of oxygen atoms or conversion of the oxygen functionalities present in biomass derivatives, which can be achieved by catalytic hydrodeoxygenation. Hydrodeoxygenation has been used to convert raw biomass-derived materials, such as biomass pyrolysis oils and lignocellulose-derived chemicals and lipids, into deoxygenated fuels and chemicals. Multifunctional catalysts composed of noble metals and transition metals supported on high surface area metal oxides and carbons, usually selected as supports of heterogeneous catalysts, have been used as efficient hydrodeoxygenation catalysts. In this review, the catalysts proposed in the literature are surveyed and hydrodeoxygenation reaction systems using these catalysts are discussed. Based on the hydrodeoxygenation methods reported in the literature, an insight for feasible hydrodeoxygenation process development is also presented. 바이오매스는 현재 석유, 천연가스, 석탄 등 화석 연료에서 얻을 수 있는 액체 연료와 유기 화합물을 생산할 수 있는 지속 가능한 대체 자원이다. 화석 연료를 사용하면 온실가스를 배출하기 때문에 바이오매스와 같은 탄소중립적 원료를 사용하는 것은 기후 변화 대응에 기여할 수 있다. 바이오매스 원료로부터 석유 대체 화학 제품과 연료를 생산하기 위한 생물학적 및 화학적 공정이 제안되었지만, 바이오매스에 포함된 높은 산소 함량때문에 화석 연료를 완전히 대체하기 어렵다. 석유와 유사한 연료와 화학 물질을 생산하려면 바이오매스 파생물에 존재하는 산소 원자를 제거하거나 산소 기능기를 전환해야 하며, 이는 촉매 화학적 수첨탈산소화에 의해 달성될 수 있다. 바이오매스 열분해 오일, 리그노셀룰로오스 유래 화학물질, 지질과 같은 원료를 탈산소 연료 및 화학물질로 전환하기 위해 수첨탈산소화가 진행되었다. 높은 표면적의 금속 산화물 또는 탄소에 지지된 귀금속 및 전이 금속으로 구성된 다기능성 촉매는 효율적인 수첨탈산소 촉매로 사용되었다. 본 총설에서는 문헌에서 제안된 촉매를 확인하고 이러한 촉매를 이용한 수첨탈산소 반응 시스템이 논의하였다. 문헌에 보고된 수첨탈산소화 방법을 기반으로, 실현 가능한 수첨탈산소화 공정 개발 방향이 제시하였다.